Mechanism-Specific Tear Film Instability Across Diabetic Retinopathy Severity: Fluorescein Break-Up Pattern Classification in Type 2 Diabetes Mellitus - Ramzi Amin; Siti Shalihah Ramadhani Novizar; Petty Purwanita (HM Publisher, 2026)
Background: Diabetic retinopathy and dry eye disease coexist in type 2 diabetes mellitus, yet conventional metrics treat tear film instability as one entity and cannot identify which layer has failed. Objective: This pilot study asked whether the Asia Dry Eye Society fluorescein break-up pattern classification tracks Early Treatment Diabetic Retinopathy Study (ETDRS) severity. Methods: Fifteen patients (30 eyes) with type 2 diabetes and any retinopathy grade were enrolled under a quota framework at RSUP Dr. Mohammad Hoesin Palembang, Indonesia, from November 2024 to July 2025. Break-up patterns were classified into five categories under cobalt-blue slit-lamp biomicroscopy on three consecutive observations; Ocular Surface Disease Index (OSDI) and tear break-up time (TBUT) were recorded. Analysis used rank correlation with exact permutation testing, proportional-odds regression and receiver operating characteristic analysis. Results: Pattern distribution differed across grades (Fisher–Freeman–Halton p = 0.007; Cramér's V = 0.536). Within the aqueous-deficiency pathway, line break progressed to area break (rho = 0.905, 95% CI 0.666–0.975, exact p = 0.002); within the decreased-wettability pathway, dimple break progressed to spot break (rho = 0.824, 95% CI 0.445–0.953, exact p = 0.009). Each one-grade increase multiplied the odds of a more severe pattern 7.442-fold (95% CI 2.555–21.673), and grade discriminated severe-mechanism patterns with an area under the curve of 0.87 (95% CI 0.681–0.955). OSDI and TBUT deteriorated monotonically (both p < 0.001), whereas random break showed no gradient (rho = 0.095, p = 0.618). Conclusion: Mechanism-specific tear film failure scales with retinopathy severity, supporting fluorescein-based tear film oriented diagnosis in Indonesian practice.